Dietary intake in youth with prader‐willi syndrome. Issue 11 (14th September 2018) - Mackenzie, Michelle L.; Triador, Lucila; Gill, Jasmeena K.; Pakseresht, Mohammadreza; Mager, Diana; Field, Catherine J.; Haqq, Andrea M.
Abstract : Dietary management is important to prevent severe obesity in individuals with Prader‐Willi syndrome (PWS); however, few studies have examined dietary intake and quality in youth with PWS. Our objective was to estimate intake of essential nutrients and diet quality in youth with PWS compared to those without PWS. Three‐day food records were used to estimate intake of energy, nutrients, nutrient‐density, foods, and adherence to healthy eating guidelines. Data were presented as medians and interquartile ranges with Mann–Whitney U and Fisher's test used to compare between groups with p < .05 considered significant. Youth with ( n = 23) and without ( n = 23) PWS were similar in age and sex distribution. The PWS group had a lower energy intake ( p ≤ .001), higher nutrient density ( p = .003), and better adherence to guidelines ( p = .007) compared to the control group. The proportion with nutrient intake from food below Estimated Average Requirement or Adequate Intake were similar between groups. Fiber, vitamin D, calcium, and potassium intake were below recommendations in 50% or more in both groups. The inclusion of supplement intake lowered the proportion below recommendations, except for fiber and potassium. Youth with PWS had a similar nutrient intake as those without PWS despite a lower energy intake, which could be attributed to higher diet quality. However, more than half of youth with PWS were at risk of inadequate fiber, vitamin D, calcium, and potassium intake. A greater emphasis on nutrient‐dense foods would improve nutrient intake, but supplements may be warranted in youth with PWS who do not meet recommendations.